Closing the SDG Financing Gap : Trends and Data - Doumbia, Djeneba; Lauridsen, Morten Lykke (International Finance Corporation, Washington, DC, 2019)
How big is the financing gap to achieve the 2030 sustainable development goals (SDGs)? Can private capital fill the gap? This note provides an updated overview of estimates of SDG financing in low- and middle-income countries and gives an analytical and data-based foundation for discussion. Based on a review of recent studies, as well as International Finance Corporation (IFC’s) own calculations of cross-border flow trends, the note documents the ongoing and significant SDG financing gap. Raising taxes to expand public spending is an option for many middle-income countries to fill the gap, but it will be insufficient for low-income countries. Private financing, especially of infrastructure, can also contribute to bridging the gap, but it will depend on the availability of investable projects. Capital market development and improved domestic financial systems can help intermediate more private capital into available investment opportunities.